2020
DOI: 10.21608/ejchem.2020.28290.2597
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, Rheological, Organoleptical and Quality Attributes of Gluten-Free Fino Bread

Abstract: Preparation and evaluation of acceptable gluten-free Fino bread (pearl millet, rice and corn flours) were targeted. Rheological properties of six blends were determined by Mixolab and Alveograph. Sensory evaluation of bread samples was done by ten mothers. The most acceptable samples were selected for chemical, antioxidant, texture, physical, microbial analysis and sensorial evaluation by 20 celiacs from Abu-Rish children's hospital. Pearl millet flour has high protein and fiber (12.11 and 2.92 %, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, the caloric values of SLSP, PMSP, and WF were 443.97, 405.15, and 404.36 (kcal/100 g). The obtained results are in agreement with those reported by AbdEl-Kader (2016), Himanshu et al (2018), Hassan et al (2020), and Mansour et al (2021).…”
Section: Nutritional Composition and Bioactive Compounds Of Raw Mater...supporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the caloric values of SLSP, PMSP, and WF were 443.97, 405.15, and 404.36 (kcal/100 g). The obtained results are in agreement with those reported by AbdEl-Kader (2016), Himanshu et al (2018), Hassan et al (2020), and Mansour et al (2021).…”
Section: Nutritional Composition and Bioactive Compounds Of Raw Mater...supporting
confidence: 93%
“…Furthermore, SLSP and PMSP are significantly (p ≤ 0.05) higher than those of WF 72%. Similar data was previously reported by Abdel-Gawad et al ( 2020) and Hassan et al (2020). The results revealed that SLSP and PMSP are considered good sources of crude protein, ether extract, ash, and crude fiber total phenolics, flavonoids, and antioxidant activity compared with these compounds in WF 72%.…”
Section: Nutritional Composition and Bioactive Compounds Of Raw Mater...supporting
confidence: 90%
“…Gluten-free products are characterized by short shelf life, and it is a challenge to obtain products that are like wheat bakery products because it is free of gluten and water does not bind as strongly with starch as it does with gluten Demirkesen and Ozkaya (2020). Hassan et al. (2020) found that millet bread staling increased with increasing storage period.…”
Section: Resultsmentioning
confidence: 99%
“…In Egypt, bread is one of the main daily food in the Egyptian diets. The Egyptian children with CD suffer from a shortage of varied and suitable gluten-free bread to achieve their needs (Hassan et al, 2020;Saccotelli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous specific circumstances, including packaging, hygienic production procedures, storage conditions, and product turnover, might be to blame for these losses (Saranraj 2010). Pan bread spoilage is a major contributor to global food waste, with fungal growth accounting for roughly 60% of pan bread spoilage cases (Hassan et al, 2020). Table 7 presents the microbial load analysis of the pan bread samples (control, xanthan gum, 1% chia flour, 2% chia flour, and 3% chia flour) stored at room temperature for 12 days to assess their shelf life.…”
Section: Assessment Of the Microbiological Quality Of Gluten-free Pan...mentioning
confidence: 99%